Tanda tangan Digital Menggunakan Algoritme Keccak dan RSA - Rezania Agramanisti Azdy (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
Just like conventional signatures, digital signatures can be used to prove the authenticity of a document in digital form. In addition, digital signatures can also be used to prove the validity of the author of the document, so that the author of the document can not deny that he had made the document. Digital signature is done by applying two cryptographic algorithms sequentially. The first algorithm is to impose hash function on a real document to produce message digest, and the second one is to impose a public key algorithm to the digest form. Keccak hash function is an algorithm that has been set as SHA-3 in a competition held by NIST and can be used to determine if a document has been modified or not. RSA is a public key algorithm which ensures the safety in the form of authentication and non-repudiation, so it is suitable with the actual purpose of digital signature. This paper implements the Keccak and RSA algorithm on digital signature as well as comparing it with the use of MD5. The test results of the implementation of both algorithms show that the establishment of digital signature on a whole process requires a relatively short time, and it is able to achieve the goals of digital signatures to guarantee the security in the aspects of integrity, authentication and non-repudiation.